Theoretical estimates of the critical exponents of the superfluid transition in 4He by lattice methods - Campostrini, Massimo; Hasenbusch, Martin; Pelissetto, Andrea; Vicari, Ettore (Physical review. B, Condensed matter and materials physics, 2006)
We improve the theoretical estimates of the critical exponents for the three-dimensional XY universality class that apply to the superfluid transition in 4He along the λ line of its phase diagram. We obtain the estimates α=−0.0151(3), ν=0.6717(1), η=0.0381(2), γ=1.3178(2), β=0.3486(1), and δ=4.780(1). Our results are obtained by finite-size scaling analyses of high-statistics Monte Carlo simulations up to lattice size L=128 and resummations of 22nd-order high-temperature expansions of two improved models with suppressed leading scaling corrections. We note that our result for the specific-heat exponent α disagrees with the most recent experimental estimate α=−0.0127(3) at the superfluid transition of 4He in a microgravity environment.
Im Titel ist die Zahl "4" hochgestellt
Gesehen am 05.07.2022